The Nature of Science in Science Education
XXII, 368 p.
Keywords: The Nature of Science in Science Education is the first book to blend a justification for the inclusion of the history and philosophy of science in science teaching with methods by which this vital content can be shared with a variety of learners. It contains a complete analysis of the variety of tools developed thus far to assess learning in this domain. This book is relevant to science methods instructors, science education graduate students and science teachers.